Computer design of a thermoelectric pulmonary air condenser with thermostating of collected condensate - Anatychuk, L.I.; Kobylianskyi, R.R.; Lysko, V.V. (Journal of Thermoelectricity, 2023)
A new design of a thermoelectric pulmonary air condenser is proposed, in which an additional thermostated chamber is used to collect condensed moisture. This allows maintaining the temperature of the collected condensate at a given permissible level to prevent its hypothermia and standardize the storage conditions. The physical model and computer model of the device are presented, the distribution of temperature and velocity of air movement in the condensate collection tube is determined depending on the temperatures of the working and additional chambers, as well as humidity, temperature and volume of exhaled air. The results of calculations of the cooling efficiency of thermoelectric modules, necessary to ensure the specified modes of operation of the device, are given.